Skrining dan Uji Diagnostik Abnormalitas Lemak pada Lansia di Kecamatan Pundong, Kabupaten Bantul - Nurbeti, Maftuhah; Rahayujati, Theodola Baning; Santosa, Tarsisius Bintarta Heru (Universitas Ahmad Dahlan, 2017)
Background: Cardiovascular diseases occupied top ten disease in Bantul district. Dyslipidemia become a major risk factor. Screening for hypercholesterolemia in Indonesia were rarely carried out and usually took urban background. Validity test of the Body Fat Analyzer (BFA) for public health screening also have not been reported. Therefore, this study aims to determine the prevalence of lipid abnormalities and the validity of BFA as a screening tool. Method: Using crosssectional design, this study was located in Pundong that had rural characteristics. With convenience sampling method, subjects were 82 elderly in 4 hamlet. Lipid abnormalities were measured by BFA. Blood cholesterol became gold standard on the cut off point of 239 mg/dl. Diagnostic test is made using 2x2 table calculation and X2 test. Results: This study found the prevalence of overweight and obesity (19.5% and 2.4%), prevalence of abnormal body faat (75.6%); prevalence of abnormal abdominal fat (20.8%); and prevalence of hypercholesterolemia (15.9%). Best validity demonstrated by the examination of a single Body Mass Index (BMI) (sensitivity 61.54%, specificity 85.51% NDP 44.44%; nd 92.19%, p=0.001). Conclusion: This result most closely approximates the prevalence in rural China. Besides being more valid, a single BMI checks are also easier and cheaper than the BFA. Therefore, the use of normal scales can be maximized. BMI measurement and interpretation should be socialized.